Triphasic dynamic contrast-enhanced computed tomography predictive model of benign and malignant risk of gallbladder occupying lesions. Issue 13 (March 2020) - Tao, Jinqiu; Zhang, Yanqiu; Chen, Huihui; Wang, Shaohe; Sun, Qi; Zhang, Wenjie; Liu, Qiaoyu; Mai, Xiaoli; Yu, Decai
Abstract : Abstract: Gallbladder occupying lesions are common diseases of biliary system. Among them, gallbladder cancer is difficult to diagnose due to the indistinguishable early symptoms, thus posing a great risk to the population. This study aims to establish a computed tomography (CT) prediction model for distinguishing benign and malignant lesions of gallbladder occupying lesions. The study included 211 patients with benign or malignant gallbladder occupying lesions who have taken resection in the Nanjing Drum Tower Hospital from January 2009 to December 2017. Clinical data collected includes age and sex; CT data includes tumor location, tumor maximum diameter, tumor form, venous phase portal venous CT value, abdominal aortic CT value, plain phase CT value, arterial phase CT value, venous phase CT value, delayed phase CT value, ΔCT1, ΔCT2, ΔCT3, ΔCT4, ΔCT5, ΔCT6, and ΔCT7 . Calculation of odds ratio between benign and malignant gallbladder occupying lesions using single factor screening variables and multivariate logistic regression was done to establish a model and calculate the areas under receiver operating characteristic curves of the model. Multivariate logistic regression analysis showed that age, tumor maximum diameter, tumor form, venous phase portal venous CT value, ΔCT2, ΔCT4, and ΔCT6 are the main characteristic index for differential diagnosis of benign and malignant risk of gallbladder occupying lesions. Patients' age, tumor maximum diameter, tumor form, venous phase portal venous CT value, ΔCT2, ΔCT4, and ΔCT6 are independent risk factors for judging the benign and malignant of gallbladder occupying lesions. The model established exhibited a potential diagnostic value for distinguishing the malignant properties of gallbladder occupying lesions.